(untitled) (Research, Society and Development, 2020)
This work discusses Ausubel’s Theory of Meaningful Learning and Vygotsky’s Proximal Development Zone concept, and his contributions to the teaching of Chemistry, articulating methodologies that encourage the participation of students in this process. Therefore, its objective is to present an approach about investigating research articulated to problem situations as a teaching method of Chemistry relating it to the theory of Meaningful Learning (AS) by David Ausubel (1980; 2000) and the concept of Proximal Development Zone (ZDP) by Lev Vygotsky (2007). The methodology used is characterized as exploratory research, based on bibliography, since it is based on analysis of books, scientific articles, monographs and dissertations. The analyzes show that these methodologies, when contextualized with the student’s reality, instigate curiosity and encourage the search for knowledge, also, when articulated to the AS and the ZDP, they facilitate the relationship between Chemistry and everyday life and the understanding of scientific concepts, favoring meaningful learning and the development of students’ autonomy.